Procedura dochodzenia wierzytelności a upadłość przedsiębiorstwa we Francji - Pastusiak, Radosław (Vindication of Claim and Company Bankruptcy Procedure in France, 2008)
Over forty thousand companies announce bankruptcy every year in France. Nevertheless the economy of this country is one of the strongest in the world. The procedure of claims' vindication in France differs from the Polish one. The main differences result from client verification procedure and complex possibilities of securing receivables before the official announcement of bankruptcy. In my opinion another important difference is that the companies in bad financial situation are not admitted for functioning, and the bankruptcy proceedings can be run ably. In France good reputation is perceived as a valuable asset.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 411-418